Modified Theories of Gravity and Cosmological Applications - Stavrinos, Panayiotis; Saridakis, Emmanuel N. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on recent aspects of gravitational theory and cosmology. It contains subjects of particular interest for modified gravity theories and applications to cosmology, special attention is given to Einstein-Gauss-Bonnet, f(R)-gravity, anisotropic inflation, extra dimension theories of gravity, black holes, dark energy, Palatini gravity, anisotropic spacetime, Einstein-Finsler gravity, off-diagonal cosmological solutions, Hawking-temperature and scalar-tensor-vector theories.